Análisis comparativo de la competitividad de las economías del Perú y Chile desde un enfoque global - Peña-Vinces, Jesús C. (2009)
Small economies, such as the Peruvian and Chilean, are immersed in the global arena of emergent economies, so evaluating them from a home based point of view (Porter, 1990) would be limited and of little use. This fact turns Porter’s national diamond framework insufficient for that purpose (Moon, Rugman and Verbeke, 1998). This paper analyzes these economies from a global view that would include local as well as foreign markets; in other words, it applies the International Competitiveness Double Diamond approach proposed by Moon, Rugman & Verbeke (1998), and Moon & Lee (2004). Information from the World Bank, the International Monetary Fund, the World Economic Forum, the Inter-American Development Bank and other sources was gathered to draw up the double diamond. The empirical analyses show that Chile is more competitive globally, while Peru is locally. To sum up, the results imply that Chile is more attractive to direct foreign investment than Peru.